Eficacia de un abordaje inicial temprano en paciente adulto con evento coronario crónico. - Carrion Prado, Dayana Carolina (Machala : Universidad Técnica de Machala, 2024)
Introduction: chronic coronary syndrome, also called stable angina pectoris, is considered a secondary response to a lack of irrigation in the epicardial vessels, caused by endothelial injury due to an atheromatous plaque. This pathology is considered of utmost importance since it is expected to have a relatively high mortality rate by 2030. Objective: To analyze the initial approach and complementary methods corresponding to chronic coronary syndrome, through the study of the most up-to-date bibliographic sources that favor the relevant diagnosis. Materials and methods: a documentary and comparative investigation of high-impact scientific articles is carried out, with a unique filter from the last 5 years, obtained from repositories such as PubMed, Science Direct, Scopus, Cochrane, among others, with the purpose of comparing results and obtaining conclusions. Development: 10 articles selected by ownership of diagnostic methods in patients with chronic coronary syndrome are compared, where concordant results are obtained regarding the initial approach, and discordant in relation to the non-invasive and invasive diagnostic method of choice. Conclusion: 100% agreement is obtained from the articles investigated on the initial approach, referring to the fact that every coronary syndrome must begin with the preparation of the practical clinical history where chest pain is specifically characterized. Divergences are obtained when choosing the most advanced diagnostic methods, however, the greatest approximation of similarity is found in 5 of 10 studies that consider single photon emission computed tomography to be elective.
Introducción: síndrome coronario crónico, o también llamado angina de pecho estable, es considerado como una respuesta secundaria a una falta de irrigación en los vasos epicárdicas, originado por la lesión endotelial a causa de una placa de ateroma. Esta patología se considera de suma importancia ya que se prevé para el 2030 tenga una tasa de mortalidad relativamente alta. Objetivo: Analizar el enfoque inicial y métodos complementarios correspondientes al síndrome coronario crónico, a través del estudio de fuentes bibliográficas más actualizadas que favorezcan el diagnóstico pertinente. Materiales y métodos: se ejecuta una investigación documental y comparativa de artículos científicos de alto impacto, con filtro único de los últimos 5 años, obtenidos de repositorios como Pubmed, Science Direct, Scopus, Cochrane, entre otros, con la finalidad de comparar resultados y obteniendo conclusiones. Desarrollo: se comparan 10 artículos seleccionados por titularidad de métodos diagnósticos en pacientes con síndrome coronario crónico, en donde se obtienen resultados concordantes en cuanto al abordaje inicial, y discordante con relación al método diagnostico no invasivo e invasivo de elección. Conclusión: se obtiene coincidencia del 100% de los artículos investigados sobre el abordaje inicial, referente a que todo síndrome coronario debe iniciarse con la elaboración de la historia clínica practica en donde se caracterice específicamente el dolor torácico. Se obtienen divergencias al momento de la elección de los métodos diagnósticos más avanzados, sin embargo, la mayor aproximación de similitud se haya en 5 de 10 estudios que consideran a la tomografía computarizada por emisión de fotón único es electiva.
Keywords: SINDROME CORONARIO CRONICO; ISQUEMIA; ANGINA ESTABLE